2014
DOI: 10.17576/jkmjc-2014-3001-10
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and the New Media Technology: A Study on Malaysian Students in Australia and United Kingdom

Abstract: This paper explores Lysgaard (1955) U-Curve model which explains the process of adaptation in a new culture. Lysgaard (1955) stated that those who migrate to other places go through the following stages of adaptation; the honeymoon stage, culture shock, adjustment and recovery. The existence and rise of new media technologies have brought the world closer together and thus raises the question whether one still go through the stages stated by Lysgaard (1955) New media components such as Twitter, Facebook, Skype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
0
7
0
2
Order By: Relevance
“…In the 1980s and the 1990s, the cost of making a telephone call to a foreign country was really expensive and communication between countries was sent via traditional postal mail. However, today, the existence of Facebook and some other social media have made communication with people across countries a lot easier (Abdul Latiff et al 2014). This experience has also shown by most of the informants in this study who are utilize social media, as well as other online media, for communication purpose and information gathering.…”
Section: The Role Of Social Media In Adaptation Processmentioning
confidence: 58%
“…In the 1980s and the 1990s, the cost of making a telephone call to a foreign country was really expensive and communication between countries was sent via traditional postal mail. However, today, the existence of Facebook and some other social media have made communication with people across countries a lot easier (Abdul Latiff et al 2014). This experience has also shown by most of the informants in this study who are utilize social media, as well as other online media, for communication purpose and information gathering.…”
Section: The Role Of Social Media In Adaptation Processmentioning
confidence: 58%
“…Although co-national friends are important for international students, it is surprising that Malay students have fewer interactions and close ties with Malaysians from different ethnic backgrounds while studying abroad as discussed in the previous studies (Ahmad, Mirza, Mohd, Pawanteh, & Salman, 2014;Weiss & Ford 2011). Weiss and Ford (2011) found that although Malay students formed more friendships with Chinese and Indian friends than they had in Malaysia, friends from other ethnic backgrounds remained a relatively small part of their close friendships as Malays tend to speak Malay among themselves and tend to speak in English with Chinese and Indian friends.…”
Section: Literature Reviewmentioning
confidence: 89%
“…Thus, as previously mentioned, the term "familiarity as a family" was introduced to describe students' close friendships when they are far from home. The concept of familiarity as a family offers some valuable insight into the concept of familiarity discussed in the studies of students living abroad (see Ahmad et al, 2014;Alazzi & Al-Jarrah, 2016;Prazeres, 2016;Weiss & Ford, 2011) as well the studies of family and friendship.…”
Section: Familiarity As a Familymentioning
confidence: 99%
See 1 more Smart Citation
“…Selain daripada aspek identiti budaya, kajian akulturasi juga telah berkembang dalam disiplin komunikasi khususnya mengenai aspek hubungan peribadi, tingkahlaku dan bentuk komunikasi para imigran di negara baharu seperti kajian Kim (1977;1978), Kim Lujan dan Dixon (1998), Inglis dan Gudykunst (1982) serta Yum (1982;1988dan Jun, 1984 (Halina Sendera, 2003). Seiring dengan perkembangan teknologi komunikasi yang melanda dunia, kajian komunikasi antara budaya juga sering dikaitkan dengan teknologi media baharu seperti kajian Tengku Siti Aisha (2018), Sabariah Mohamed Salleh dan Siti Khadijah Hussin (2017), serta Abdul Latiff Ahmad et al (2014).…”
Section: Pengenalanunclassified